KOLABORASI ORANG TUA DAN GURU MEMBANGUN KEMANDIRIAN ANAK USIA DINI - Saudah, Saudah; Sri Hidayati; Resti Emilia (NANAEKE: Indonesian Journal of Early Childhood Education, 2022)
This study aims to describe the collaboration of parents and teachers in building the independence of early childhood in the limited face-to-face learning (PTM) period. This study used a qualitative descriptive method with data collection techniques, namely non-participatory observation, structured interviews with 1 teacher, 5 parents and 5 children in Al-Firdaus Kindergarten Palangka Raya which were used as data sources. The results showed that the collaboration of parents and teachers builds children’s independence through activities that children do every day either at home or at school. The scope of activities in building children’s independence includes: First, physical activity, namely getting children used to doing activities independently, for example: brushing teeth, eating and wearing clothes. Second, foster a sense of self-confidence such as: teaching children to express their desires. Third, build a sense of responsibility such as: training children to complete school assignments. Fourth, get used to being disciplined such as: biasing disciplined children to come to school and. Fifth, socialize, by providing opportunities for children to interact with their friends. Six, controlling emotions, by teaching children to be patient when their desires have not been fulfilled.